Pengaruh Penyaluran Kredit terhadap Pendapatan Operasional BRI Unit Bumi Waras Bandar Lampung - Niar Azriya; Eka Travilta Oktaria (Universitas Mitra Indonesia, 2020)
Bank is a company that engages in finance, meaning that banking activity is always related in finance, namely to raise funds from the wider community and then the funds are re-played or re-sold to the community in the form of loans or better known as credit terms. The purpose of this research is to determine the influence of working capital credit, investment credit, as well as the dominant influence of both types of credit to the Bank's operating income. This type of research is quantitative, while the population in this research is the credit channeled by BRI Unit Bumi Waras Period 2009 – 2014. The testing equipment used in this study is a simple linear regression analysis, classic assumption Test, hypothesis testing. Simultaneously, working capital and investment credit are positively and significantly influential in the operating income of BRI Unit Bumi Waras. Partial working capital credit and investment credit are influential and significant to the operating income of BRI Unit Bumi Waras and the variable of working capital credits most dominant to revenue.